Factors Influencing Procrastination of 2021 Class Student in Completing Academic Assignments at Dhyana Pura University - Budiman, Sebastian Ryan; Wiriana; Dewi, Ni Nyoman Ari Indra (LPPM Universitas Dhyana Pura, 2025)
Academic procrastination is a common phenomenon among college students and is influenced by various internal and external factors. This study aims to identify factors that influence students' procrastination behavior in completing academic assignments using Zimmerman's Self-Regulation Theory as an analytical tool. This study is a type of qualitative research with data collection methods through in-depth interviews. The results of the study indicate that internal factors, such as lack of self-control and anxiety about the quality of work, play a major role in encouraging students to procrastinate. Meanwhile, external factors, such as an unsupportive environment and the influence of friends who invite them to do other activities, also contribute to the habit of procrastination. To overcome procrastination, students need to build self-motivation, create effective time planning, and utilize social support from friends or partners to remind each other of assignment deadlines. This study recommends intervention strategies based on self-regulation and social support to reduce the habit of procrastination.